Risk Factors in Post-LASIK Corneal Ectasia - Tatar, Mehmet Gurkan (Hindawi Publishing Corporation, 2014)
Purpose. To evaluate the risk factors for post-laser in situ keratomileusis (LASIK) ectasia. Materials and Methods. Medical records of 42 eyes of 28 (10 women, 18 men) patients who developed corneal ectasia after LASIK were retrospectively reviewed. Topographical features and surgical parameters of those patients were evaluated. Results. The mean age of patients was 34.73 ± 6.50 (23–48) years and the mean interval from LASIK to the diagnosis of post-LASIK ectasia was 36.0 ± 16.92 (12–60) months. The following factors were determined as a risk factors: deep ablation (>75 μm) in 10 eyes, FFK (forme fruste keratoconus) in 6 eyes, steep cornea (>47 D) in 3 eyes, pellucid marginal degeneration (PMD) in 2 eyes, thin cornea (<500 μm) in 2 eyes, thin and steep cornea in 2 eyes, thin cornea and deep ablation in 5 eyes, FFK and steep cornea in 2 eyes, and FFK, steep cornea, and deep ablation in 1 eye. However no risk factor has been determined in 9 eyes (21.4%). Conclusion. The findings of our study showed that most of the patients who developed post-LASIK ectasia have a risk factor for post-LASIK ectasia. However, the most common risk factor was deep ablation.